Psychological aspects of excimer laser surgery for myopia: reasons for seeking treatment and patient satisfaction. Issue 10 (October 1996) - McGhee, C N; Orr, D; Kidd, B; Stark, C; Bryce, I G; Anastas, C N
Abstract : AIMS: To determine the reasons patients seek excimer laser treatment for myopia and to measure levels of patient satisfaction with each phase of this relatively new treatment. METHODS: A unique 38 item visual analogue questionnaire was developed and applied to 100 consecutive patients (n = 100) who had undergone excimer laser photorefractive keratectomy for myopia or myopic astigmatism at a single centre. All subjects underwent extensive ophthalmic assessment and patient education before treatment. RESULTS: A 90% response rate was achieved (n = 90). Improved unaided vision (85.6%), freedom from spectacles (83.3%), and difficulties with contact lens wear (72.7%) were the most common reasons for seeking treatment. The majority of patients felt that the quality of their life had improved (85.5%) and 82% felt that the quality of their unaided vision was as good as they had anticipated. overall, 95.5% of patients were pleased that they had undergone this procedure. The vast majority (98.9%) of patients felt that they fully understood the operation pretreatment but almost one quarter (23.9%) found the actual operation distressing. Only 15.7% found postoperative pain did not respond adequately to prescribed analgesia. CONCLUSIONS: This study demonstrates a very high level of patient satisfaction after excimer laser treatment for myopia and myopic astigmatism. It suggests that most patients seek treatment to enjoy better vision free from optical aids and that a high level of patient education preoperatively may establish realistic expectations and satisfaction with overall outcome.